ENERGY SAVING TECHNOLOGY OF LIGATURES PRODUCTION ON THE BASIS OF MOLYBDENUM - A. G. Slutsky; A. S. Kalinichenko; V. A. Sheynert (Литьë и металлургия)
Data on development of technology of the molybdenum-containing addition alloy production by method of aluminothermic restoration is provided in the article. Influence of conditions of production on quality and metallurgical output of addition alloy is studied. The received addition alloys were tested in industrial conditions at smelting of the low-alloyed steel 35HML and the received results confirmed efficiency of application of the developed addition alloy.